Passive optical network (PON) supported networking - De Andrade, Marilet; Maier, Martin; McGarry, Michael P.; Reisslein, Martin (Optical switching and networking, 2014)
In this editorial, we first set the context for the subject matter of this special issue on passive optical network (PON) supported networking. This context includes a discussion of optical networking in all segments of a global communication network and the emphasis of the importance of PONs in the access network as well as their role supporting other communication network technologies. We follow this broader context with an introduction to the articles appearing in this special issue. Lastly, we conclude this editorial with a broad outlook to the future of PONs in communication networks.